Practicing Diversity in Higher Education in Geography: Exploring Spaces of Diversity and Their Barriers in a Geography Department in Switzerland. Issue 1 (2nd January 2023) - Jokela-Pansini, Maaret; Wintzer, Jeannine
Abstract : Recent feminist geographic scholarship has urged geographers to distance themselves from androcentric and Eurocentric approaches, and to open up the discipline to diverse perspectives. Whereas numerous studies have focused on diversifying and decolonizing geography through recruitment practices, mentoring, and knowledge production, only a few have analyzed how diversity translates into teaching practices, particularly in contexts where diversity is relatively well-established among staff. Based on a questionnaire survey among the teaching staff, a content analysis of course syllabi, and a quantitative analysis of the department's employee data, this article explores to what extent diversity within the department leads to diversity in teaching practices. By developing a framework of spaces of diversity, we analyze three spaces that potentially enable practicing diversity in teaching: The department's academic space promotes free choice of research and teaching topics and flexible working conditions; the department space enables individuals to engage in shaping geographical teaching; and the knowledge space promotes diversity as an ideal. We found, however, that practicing diversity in geography is challenged through traditional and neoliberal university structures and formal and perceived hierarchies. Moreover, there is a need for concrete diversity practices on individual and institutional levels to actively bring diverse perspectives into the classroom.